Information Security Policies’ Compliance in Higher Education Institutions - HINA, SADAF (2018)
Higher education institutions (HEI) are progressively computerized to deal with substantial academic and operational information. This academic sector is advancing in implementation of technical security controls, however behavioral influence is still a challenge in information security domain. Information security policies (ISPs) are generally designed and developed to control employees’ working behavior, yet compliance with these documents is near to non-existence. This study reports that information security policies’ compliance (ISPC) in HEIs remains scarce, as is the realization of security threats and dissemination of ISPs to end-users (employees).